2012
DOI: 10.1111/j.1477-2574.2012.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Staged hepatectomy for bilobar colorectal hepatic metastases

Abstract: In patients in whom staged resection for bilobar CRLM is feasible, surgery would appear to offer benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Although all patients underwent a potentially curative resection, 73% of them subsequently developed recurrent disease. Reported 5‐year OS data in some modern series reaches 60% in selected patients . However, the current study presents actual rather than actuarial survival data.…”
Section: Discussionmentioning
confidence: 80%
“…Although all patients underwent a potentially curative resection, 73% of them subsequently developed recurrent disease. Reported 5‐year OS data in some modern series reaches 60% in selected patients . However, the current study presents actual rather than actuarial survival data.…”
Section: Discussionmentioning
confidence: 80%
“…Following PVO in a patient with bilateral liver metastasis, the risk of tumor progression is increased in the FLR, which results in an overall 52%-80% resection rate for traditional two-stage hepatectomy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analysis showed that age over 70 years, male gender, larger lesions >5 cm, serum carcinoembryonic antigen level before PVE greater than 200 ng/ml, and three or more metastases in the FRL were significant factors predicting failure to achieve two-stage hepatectomy (TSH). Multivariable logistic regression analysis showed the presence of extrahepatic disease, three or more metastases in the FRL, and patient age above 70 years to be factors associated with the failure of staged resection [26,27]. The main reasons for the non-completion of the second stage are tumor progression, followed by insufficient hypertrophy of the remnant liver and portal vein thrombosis of FLR.…”
Section: Two-stage Liver Resection With Portal Vein Embolizationmentioning
confidence: 98%